Reproductive aging in biological females: mechanisms and immediate consequences - Muhammad, Yasin Ali (Frontiers in Endocrinology, 2025)
Reproductive aging is a dynamic, systemic process that encompasses more than the decline in ovarian function. It involves coordinated changes across neuroendocrine, immune, metabolic, and mitochondrial systems. Central to this transition is the depletion of ovarian follicles, leading to reduced estradiol and progesterone production and subsequent disruption of the hypothalamic-pituitary-gonadal (HPG) axis. This hormonal shift remodels hypothalamic signaling networks - particularly those involving kisspeptin, neurokinin B (NKB), and GABA - driving alterations in gonadotropin-releasing hormone (GnRH) pulsatility, vasomotor symptoms (VMS), and loss of reproductive cycling. Simultaneously, chronic inflammation, oxidative stress, and mitochondrial dysfunction further accelerate both ovarian and neural aging. Estrogen receptor subtypes (ERα and ERβ) play critical and region-specific roles in mediating tissue responses to hormonal withdrawal, contributing to variability in symptom expression and therapeutic outcomes. Genetic, cultural, and environmental factors - such as diet, endocrine disruptors, and APOE genotype - further influence the trajectory and severity of menopause-related changes. Emerging treatments, including neurokinin receptor antagonists and ERβ-selective modulators, offer targeted alternatives to conventional hormone therapy. This review frames menopause not as a singular endocrine endpoint but as a neuroimmune transition, highlighting the need for mechanistic insight and personalized therapeutic approaches to improve health outcomes during reproductive aging.